2010
DOI: 10.1128/aac.00414-10
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the adeB Gene in Clinical Isolates of Tigecycline-Nonsusceptible Acinetobacter baumannii without Insertion Mutations in adeRS

Abstract: Thirteen clinical isolates of multidrug-resistant Acinetobacter baumannii resistant to carbapenems (MRAB-C) with tigecycline nonsusceptibility were collected from individual patients in this study. None of the 13 isolates shared the same strain characteristics in molecular typing. All of them showed increased adeB transcription, as predicted. However, none of these tigecycline-nonsusceptible MRAB-C isolates were found to possess previously known adeRS mutations. Upregulation of adeB transcription may result fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
4
39
0
Order By: Relevance
“…Overexpression of AdeABC has been shown to confer reduced susceptibility to tigecycline (2,6,10,14,15,16). Thirteen of the 14 clinical isolates had a tigecycline MIC of Ն0.5 g/ml (Table 1) and were considered resistant (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of AdeABC has been shown to confer reduced susceptibility to tigecycline (2,6,10,14,15,16). Thirteen of the 14 clinical isolates had a tigecycline MIC of Ն0.5 g/ml (Table 1) and were considered resistant (23).…”
Section: Resultsmentioning
confidence: 99%
“…An A 94 V substitution in AdeS was found in an A. baumannii isolate from a patient receiving tigecycline therapy that resulted in 6-fold adeB overexpression and an increase in the tigecycline MIC from 0.5 to 16 g/ml compared to the susceptible strain isolated previously from the same patient (14); however, because of the presence of additional single nucleotide polymorphisms (SNPs) between the two strains, the possibility of nonisogenic clinical isolates was raised (15). Lately, no AdeRS mutations were found in 13 unrelated MDR A. baumannii isolates with increased AdeABC expression and decreased tigecycline susceptibility (16).…”
mentioning
confidence: 99%
“…In addition, although no direct evidence of the role of the porins OmpA and OprD in antimicrobial resistance has been demonstrated, the observed changes may act on their functionality and, thus, on membrane permeability to several antimicrobial compounds. Similarly, we have analyzed the sequence of efflux pump regulatory genes, which are known to be involved in antibiotic resistance, namely, the AdeR/S two-component system and AdeN and AdeB, which regulate the AdeIJK and AdeAB efflux pumps, respectively (35)(36)(37). Although only a few substitutions were found in efflux pump regulatory genes, further investigations using reverse transcription-PCR will be necessary to correlate these substitutions with overexpression of these efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the absence of an adeB gene knockout experiments, it is difficult to ascertain the overall contribution of the AdeABC efflux pump to tigecycline nonsusceptibility (Peleg et al, 2007;Hornsey et al, 2010). But, one recent study demonstrated that overexpression of the adeABC efflux pump resulted in tigecycline nonsusceptibility by quantizing transcripts of the adeB gene and demonstrating conversion of the tigecycline resistance pattern in the presence of an efflux pump inhibitor without any previously known mutation (Sun et al, 2010). When the isolates were analysed separately, there was an association between a higher MIC and elevated adeABC expression, although more isolates would need to be investigated to confirm this observation.…”
Section: Rnd Type Efflux Pumpmentioning
confidence: 99%